Trifluoromethyl Boron Dipyrromethene Derivatives as Potential Photosensitizers for Photodynamic Therapy - Liu, Jian-Yong (Molecules, 2018)
In this study, two novel boron dipyrromethene-based photosensitizers (BDP3 and BDP6) substituted with three or six trifluoromethyl groups have been synthesized and characterized with various spectroscopic methods, and their photo-physical, photo-chemical, and photo-biological properties have also been explored. The two photosensitizers are highly soluble and remain nonaggregated in N,N-dimethylformamide as shown by the intense and sharp Q-band absorption. Under red light irradiation (λ = 660 nm, 1.5 J/cm(2)), both photosensitizers show high and comparable cytotoxicity towards HepG2 human hepatocarcinoma and HeLa human cervical carcinoma cells with IC(50) values of 0.42–0.49 μM. The high photocytotoxicity of BDP3 and BDP6 can be due to their high cellular uptake and low aggregation tendency in biological media, which result in a high efficiency to generate reactive oxygen species inside the cells. Confocal laser fluorescence microscopic studies indicate that they have superior selective affinities to the mitochondria and lysosomes of HepG2 and HeLa cells. The results show that these two trifluoromethyl boron dipyrromethene derivatives are potential anticancer agents for photodynamic therapy.